Cognitive functioning and treatment outcomes in a randomized controlled trial of internet‐delivered drug and alcohol treatment. (9th August 2018) - Shulman, Matisyahu; Campbell, Aimee; Pavlicova, Martina; Hu, Mei‐Chen; Aharonovich, Efrat; Nunes, Edward V.
Abstract : Background and Objectives: Substance use disorders are associated with lower cognitive functioning, and this impairment is associated with poorer outcomes. The Therapeutic Education System (TES) is an internet‐based psychosocial intervention for substance use disorders that may provide enhanced treatment for individuals with cognitive deficits. This secondary analysis investigates the association between cognitive functioning and treatment outcomes in a large ( N = 507) randomized controlled effectiveness trial of TES compared to treatment‐as‐usual conducted within outpatient programs in the National Drug Abuse Treatment Clinical Trials Network. Methods: All participants completed a computer‐based cognitive assessment (Microcog™ short version) at baseline. Scores on subtests of attention, reasoning, and spatial perception were tested as moderators of the treatment effect on abstinence and retention at the end of the 12‐week treatment phase using mixed effects logistic regression. Results: Cognitive functioning was not found to be a moderator of treatment on abstinence or retention. Post‐hoc analysis of the main effect of cognitive functioning on retention and abstinence found impaired reasoning and cognitive flexibility were associated with lower retention. There were no other main effects of cognitive functioning on retention or abstinence. Conclusions: The benefit of internet delivered treatment over standard care was unchanged across a range of cognitive functioning. Consistent with previous research, mild to moderate impairment in reasoning and cognitive flexibility were associated with lower retention across both treatment arms. Scientific Significance: An internet‐delivered cognitive behavioral intervention for substance use disorders, TES, is equally effective across a spectrum of cognitive functioning among diverse patients. (Am J Addict 2018;27:509–515)